2012
DOI: 10.3109/10428194.2012.731599
|View full text |Cite
|
Sign up to set email alerts
|

Orphan receptor tyrosine kinases ROR1 and ROR2 in hematological malignancies

Abstract: The receptor tyrosine kinase ROR1 has been shown to be overexpressed in chronic lymphocytic leukemia (CLL). The aim of this study was to further characterize the expression of ROR1 and the other member of the ROR family, ROR2, in other lymphoid and myeloid malignancies. Normal white blood cells and reactive lymph nodes were negative for ROR1 and ROR2. A significantly high and uniform surface expression of ROR1 was found in CLL/hairy cell leukemia (HCL) compared to mantle cell lymphoma (MCL), marginal zone lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 32 publications
4
70
0
5
Order By: Relevance
“…Evaluation of serial samples revealed that the expression levels of ROR1 did not vary substantially over time, as noted in a prior study. 19 However, this earlier study also noted an increase in the frequency of ROR1 Pos CLL cells had enhanced activation of AKT signaling pathways, we found that ratios of activated AKT (phosphorylated AKT) to total AKT in ROR1 Pos CLL were higher than those of ROR1 Neg CLL samples. Such differences were comparable to those noted between the ROR1 Pos leukemia of ROR1xTCL1 transgenic mice relative to the ROR1 Neg leukemia that develops in otherwise syngeneic TCL1 transgenic mice.…”
Section: Discussionmentioning
confidence: 36%
“…Evaluation of serial samples revealed that the expression levels of ROR1 did not vary substantially over time, as noted in a prior study. 19 However, this earlier study also noted an increase in the frequency of ROR1 Pos CLL cells had enhanced activation of AKT signaling pathways, we found that ratios of activated AKT (phosphorylated AKT) to total AKT in ROR1 Pos CLL were higher than those of ROR1 Neg CLL samples. Such differences were comparable to those noted between the ROR1 Pos leukemia of ROR1xTCL1 transgenic mice relative to the ROR1 Neg leukemia that develops in otherwise syngeneic TCL1 transgenic mice.…”
Section: Discussionmentioning
confidence: 36%
“…Monoclonal antibodies to ROR1 and frizzled domain showing cytotoxicity have been demonstrated in cell lines. Inhibition of tyrosine kinase or immunotargeting of ROR1 molecule also could be prospective in the treatment of cancers [8,9]. In this study, we firstly revealed that ROR1 is highly expressed in gastric adenocarcinoma and ROR1 could be a possible target for gastric cancer therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Although the expression of ROR1 is low in mature human tissues, some subsequent studies have revealed that ROR1 is expressed in cancer cells. In some blood malignancies including chronic lymphocytic leukemia, chronic myelogenous leukemia, and diffuse large B-cell lymphoma, expression of ROR1 was observed [8,9]. High expression of ROR1 is also observed in many solid malignancies such as colon, lung, pancreatic, prostate, and breast cancer tissues [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…This differential expression pattern, low ROR1 expression in adult tissue and high expression in cancer have led investigators to examine the functional advantage conferred to cancer by ROR1 expression and to explore the use of immune-based therapies against ROR1 for targeting cancer cells. (Baskar et al, 2008; Barna et al, 2011; Zhang et al, 2012a; Zhang et al, 2012b; Daneshmanesh et al, 2013)…”
Section: Ror1 In Cancermentioning
confidence: 99%